Technological Change and the Right to Strike - Woods, H. (Relations industrielles / Industrial Relations, 1972)
A collective agreement covers only part of the relationship between the employees covered by the agreement and the employer. Some conflicts of interest not covered by the agreement may be resolved voluntarily by negotiation from time to time, but there remain conflicts of interest in which either no resolution can be worked out on one party, the employer, supported by the residual rights doctrine and the agreement, refuses to negotiate. The issue has become a matter of great public controversy in Canada in recent years and was highlighted by the technological change debate.